Characteristics of Serial Peripheral Interfaces (SPI) timing parameters for optical mouse sensor - Mohd Khairuddin, Md Arshad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org